Surface modification method of magnesium-lithium alloy

The uniform microarc oxide layer was formed by microarc oxidation method, and combined with the method of sealing and spraying the paint layer, the problem of insufficient protection and humidity resistance after surface modification of magnesium lithium alloy was solved, and the corrosion resistance and weather resistance of magnesium lithium alloy was significantly improved.

CN119530925APending Publication Date: 2025-02-28XIAN AEROSPACE TIMES PRECISION ELECTROMECHANICAL CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411635040.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing surface modification methods of magnesium lithium alloys have problems such as poor protection performance or uneven film thickness, resulting in insufficient corrosion resistance and moisture and heat resistance of magnesium lithium alloys.

Method used

The surface of magnesium lithium alloy is modified by microarc oxidation method. By energizing the microarc oxidation electrolyte for microarc oxidation, a uniform microarc oxidation layer is formed. After the sealing treatment, a special primer for magnesium alloy and acrylic polyurethane topcoat are sprayed to form a solid sealing layer and paint layer.

Benefits of technology

It improves the protection and humidity resistance of magnesium lithium alloy, can effectively prevent corrosion in humid and heat environment, and extends the service life of magnesium lithium alloy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119530925A_ABST
    Figure CN119530925A_ABST
Patent Text Reader

Abstract

The invention provides a surface modification method of a magnesium-lithium alloy, which can solve the problems that the protection performance of the modified magnesium-lithium alloy is poor, or the thickness of a film layer is not uniform in a micro-arc oxidation process, and the humidity and heat resistance of the modified magnesium-lithium alloy is poor in an existing modification method. The method comprises the following steps: pretreating a magnesium-lithium alloy body; preparing a micro-arc oxidation electrolyte; carrying out micro-arc oxidation treatment to obtain the magnesium-lithium alloy with a micro-arc oxidation layer on the surface; cleaning and drying the magnesium-lithium alloy subjected to micro-arc oxidation treatment, pre-baking, spraying the surface of the magnesium-lithium alloy with a silane confining liquid, baking, turning over, spraying the unsprayed surface of the magnesium-lithium alloy with the silane confining liquid, curing, and cooling to room temperature to obtain the magnesium-lithium alloy with a hole sealing layer on the surface; spraying a special primer for magnesium alloy and baking to obtain the magnesium-lithium alloy with a primer layer on the surface; and spraying acrylic polyurethane finishing paint and baking to obtain the magnesium-lithium alloy with a finishing paint layer on the surface, carrying out a damp-heat test, judging whether the magnesium-lithium alloy is qualified or not, and finishing the surface modification of the magnesium-lithium alloy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a surface modification method of a metal material, in particular to a surface modification method of a magnesium-lithium alloy. Background Art

[0002] Magnesium-lithium alloy is called "ultra-light alloy". It not only has high specific rigidity, high elastic modulus, good machinability, and low anisotropy, but also has good magnetic shielding and shockproof performance. Normally, in the electrochemical corrosion process of magnesium alloy, magnesium (Mg) always corrodes and dissolves first as the anode. However, in magnesium-lithium alloy, the standard electrode potential of Mg is -2.73V, and the standard electrode potential of lithium (Li) is -3.045V. The electronegativity of Li is greater than that of Mg. In the electrochemical corrosion process of magnesium-lithium alloy, Li always corrodes and dissolves first as the anode. Therefore, the corrosion resistance of magnesium-lithium alloy is lower than that of other magnesium alloys. When magnesium-lithium alloy is in a humid atmosphere, its stress corrosion sensitivity is very large. When it is in the atmosphere at room temperature, it will also suffer from severe corrosion. Therefore, corrosion resistance is the main factor restricting the widespread application of magnesium-lithium alloy.

[0003] In order to improve the corrosion resistance of magnesium-lithium alloy, chemical oxidation and micro-arc oxidation are usually used to modify the surface of magnesium-lithium alloy. Among them, the problem of using chemical oxidation to modify the surface of magnesium-lithium alloy is that the chemical oxidation film layer generated on the surface of magnesium-lithium alloy is relatively thin, resulting in poor protection performance of the modified magnesium-lithium alloy. The problem of using micro-arc oxidation to modify the surface of magnesium-lithium alloy is that the film thickness during the micro-arc oxidation process is uneven, and the moisture and heat resistance of the modified magnesium-lithium alloy is poor. Summary of the invention

[0004] The purpose of the present invention is to solve the technical problems that the existing surface modification methods of magnesium-lithium alloys have poor protective performance of the modified magnesium-lithium alloy, or the film thickness is uneven during the micro-arc oxidation process, and the moisture and heat resistance of the modified magnesium-lithium alloy is poor, and to provide a surface modification method for magnesium-lithium alloys.

[0005] In order to achieve the above object, the present invention adopts the following technical solution:

[0006] A surface modification method for a magnesium-lithium alloy comprises the following steps:

[0007] Step 1, pretreating the magnesium-lithium alloy body;

[0008] Step 2, dissolving vanadate, fluoride and phosphate in deionized water to prepare a micro-arc oxidation electrolyte; wherein the mass fraction of vanadate is 8-10%, the mass fraction of fluoride is 8-10%, and the mass fraction of phosphate is 28-32%;

[0009] Step 3, using the magnesium-lithium alloy body pretreated in step 1 as an anode and the inert metal plate as a cathode, immersing the anode and the cathode in the micro-arc oxidation electrolyte to form an electrolytic cell; then energizing the electrolytic cell to perform micro-arc oxidation treatment to obtain a magnesium-lithium alloy with a micro-arc oxidation layer on the surface;

[0010] Step 4: Sealing

[0011] Step 4.1, cleaning and drying the magnesium-lithium alloy after micro-arc oxidation treatment in step 3;

[0012] Step 4.2, pre-baking the magnesium-lithium alloy dried in step 4.1, then spraying the surface of the magnesium-lithium alloy with a silane sealing liquid, and baking it, turning it over, spraying the unsprayed surface of the magnesium-lithium alloy with a silane sealing liquid, and curing it, and finally cooling it to room temperature to obtain a magnesium-lithium alloy with a sealing layer on the surface;

[0013] Step 5: Spray treatment and wet heat test

[0014] Step 5.1, spraying the surface of the magnesium-lithium alloy obtained in step 4.2 with a special primer for magnesium alloy, and baking, after cooling to room temperature, repeating the spraying and baking operations once to obtain a magnesium-lithium alloy with a primer layer on the surface;

[0015] Step 5.2, spraying the surface of the magnesium-lithium alloy obtained in step 5.1 with an acrylic polyurethane topcoat, baking, cooling to room temperature, repeating the spraying and baking operations once, and obtaining a magnesium-lithium alloy with a topcoat layer on the surface;

[0016] Step 5.3, perform a wet heat test on the magnesium-lithium alloy obtained in step 5.2 to determine whether it is qualified. If not, the magnesium-lithium alloy is treated as waste, and a new magnesium-lithium alloy body is selected, and the process returns to step 1 until the current magnesium-lithium alloy passes the wet heat test; if so, the surface modification of the magnesium-lithium alloy is completed.

[0017] Furthermore, step 4.2 is specifically as follows:

[0018] Under the condition of pre-baking temperature of 105-115°C, the magnesium-lithium alloy dried in step 4.1 is pre-baked for 10-20 minutes, and then the surface of the magnesium-lithium alloy is sprayed with silane sealing liquid, and baked for 5-10 minutes under the condition of baking temperature of 105-115°C. After turning over, the unsprayed surface of the magnesium-lithium alloy is sprayed with silane sealing liquid again, and cured at a curing temperature of 165-175°C and a curing time of 30-40 minutes. Finally, it is cooled to room temperature to obtain a magnesium-lithium alloy with a sealing layer on the surface, and the thickness of the sealing layer is 1μm to 3μm.

[0019] Furthermore, step 3 specifically includes the following steps:

[0020] Step 3.1, using the magnesium-lithium alloy body pretreated in step 1 as an anode and an inert metal plate as a cathode, immersing the anode and the cathode in the micro-arc oxidation electrolyte to form an electrolytic cell;

[0021] Step 3.2: Use a single pulse power supply to energize the electrolytic cell and control the current density to be 1.5-2.5 A / dm 2 , the frequency is 300-400 Hz, and the temperature of the micro-arc oxidation electrolyte is 20-25° C. The anode is subjected to micro-arc oxidation treatment for 8-10 minutes to obtain a magnesium-lithium alloy with a micro-arc oxidation layer on the surface, and the thickness of the micro-arc oxidation layer is 20 μm-25 μm.

[0022] Further, step 5.1 is specifically to spray the surface of the magnesium-lithium alloy obtained in step 4.2 with a magnesium alloy special primer with a viscosity of 18 to 22s, and then bake it at a temperature of 95 to 105°C for 50 to 70 minutes, and after cooling to room temperature, repeat the spraying and baking operations once to obtain a magnesium-lithium alloy with a primer layer on the surface, and the thickness of the primer layer is 30 μm to 40 μm;

[0023] Specifically, step 5.2 is to spray the surface of the magnesium-lithium alloy obtained in step 5.1 with an acrylic polyurethane topcoat with a viscosity of 18 to 24s, and then bake it at a temperature of 95 to 105°C for 50 to 70 minutes. After cooling to room temperature, the spraying and baking operations are repeated once to obtain a magnesium-lithium alloy with a topcoat layer on the surface. The total thickness of the topcoat layer and the primer layer is 80 μm to 120 μm.

[0024] Furthermore, step 5.3 specifically includes the following steps:

[0025] Step A1, placing the magnesium-lithium alloy obtained in step 5.2 into a wet heat test chamber, and setting the initial temperature of the chamber to 30° C.;

[0026] Step A2: within 2 hours, the temperature in the box is raised from 30°C to 60±2°C, and the relative humidity is raised to 95%, and then maintained at 60±2°C and 95% for 6 hours;

[0027] Step A3, within 8 hours, the temperature in the box is cooled from 60±2°C to 30±2°C, and the relative humidity is maintained above 85% during the cooling period. When the temperature drops to 30±2°C, the relative humidity is controlled to 95%, and maintained at this temperature and relative humidity for 8 hours;

[0028] Step A4, repeat step A2 and step A3 until at least 10 cycles are completed, take out the magnesium-lithium alloy, and determine whether it is qualified. If not, the magnesium-lithium alloy is treated as waste, and a magnesium-lithium alloy body is reselected, and return to step 1 until the current magnesium-lithium alloy passes the wet heat test; if so, the surface modification of the magnesium-lithium alloy is completed.

[0029] Furthermore, step 2 is specifically as follows:

[0030] Sodium vanadate, sodium fluoride and sodium phosphate are dissolved in deionized water to prepare a micro-arc oxidation electrolyte; wherein the mass fraction of sodium vanadate is 8%, the mass fraction of sodium fluoride is 8%, and the mass fraction of sodium phosphate is 30%.

[0031] Furthermore, step 4.2 is specifically as follows:

[0032] Under the condition of pre-baking temperature of 110°C, the magnesium-lithium alloy dried in step 4.1 is pre-baked for 15 minutes, and then the surface of the magnesium-lithium alloy is sprayed with silane sealing liquid. Under the condition of baking temperature of 110°C, it is baked for 8 minutes. After turning over, the unsprayed surface of the magnesium-lithium alloy is sprayed with silane sealing liquid again, and cured at a curing temperature of 170°C and a curing time of 35 minutes. Finally, it is cooled to room temperature to obtain a magnesium-lithium alloy with a sealing layer on the surface, and the thickness of the sealing layer is 1μm to 3μm.

[0033] Furthermore, step 3.2 is specifically as follows:

[0034] The electrolytic cell was energized by a single pulse power supply, and the current density was controlled to be 1.5A / dm 2 , the frequency is 300 Hz, and the temperature of the micro-arc oxidation electrolyte is 20° C. The anode is subjected to micro-arc oxidation treatment for 10 minutes to obtain a magnesium-lithium alloy with a micro-arc oxidation layer on the surface, and the thickness of the micro-arc oxidation layer is 20 μm to 25 μm.

[0035] Furthermore, in step 5.1, the viscosity of the magnesium alloy special primer is 18s, the baking temperature is 100°C, and the baking time is 1h;

[0036] In step 5.2, the viscosity of the acrylic polyurethane topcoat is 18s, the baking temperature is 100°C, and the baking time is 1h.

[0037] Furthermore, step 1 is specifically as follows:

[0038] The magnesium-lithium alloy body is machined into a preset size and then degreased, cleaned and dried in sequence.

[0039] Beneficial effects of the present invention:

[0040] 1. The surface modification method of a magnesium-lithium alloy provided by the present invention has a simple operation process and can improve the protective performance and moisture and heat resistance of the magnesium-lithium alloy. Under the moisture and heat state, temperature and moisture will not corrode the metal layer, thereby improving the weather resistance of the entire product, reducing the corrosion rate of the magnesium-lithium alloy, and improving the applicability of the magnesium-lithium alloy material.

[0041] 2. During the micro-arc oxidation treatment, the present invention sets certain parameters such as current, frequency and time to make the micro-arc oxidation layer uniform and have good thickness consistency. The micro-arc oxidation layer is then sealed with a sealing liquid to fill the micropores of the micro-arc oxidation layer. The filled film layer is not easy to absorb the atmosphere and moisture in the air. After sealing, a special primer for magnesium alloy and an acrylic polyurethane topcoat are sprayed in sequence. The primer has good bonding force with the micro-arc oxidation layer and the sealing layer, and has a certain protective effect on the magnesium-lithium alloy. The topcoat and the primer have good matching properties. The two paint layers are firmly combined with the micro-arc oxidation layer and the sealing layer to block the atmosphere and moisture in the air.

[0042] 3. In the sealing process of the present invention, the method of spraying the sealing liquid is adopted, which can save time and labor costs. By setting appropriate process parameters and performing pre-baking, baking and curing in sequence, the sealing layer is made uniform and continuous without accumulation, bottom exposure, wrinkles and excess impurities.

[0043] 4. The magnesium-lithium alloy is modified by the method of the present invention so that the surface of the modified magnesium-lithium alloy can pass 10 cycles of wet heat test. After the wet heat test, the surface of the magnesium-lithium alloy has no defects such as discoloration, peeling, blistering, corrosion, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 It is a schematic diagram of the appearance of a magnesium-lithium alloy body after pretreatment in step 1 of an embodiment of a method for surface modification of a magnesium-lithium alloy of the present invention;

[0045] Figure 2 Schematic diagram of the appearance of the magnesium-lithium alloy with a micro-arc oxidation layer on the surface obtained in step 3 of an embodiment of the present invention;

[0046] Figure 3 Schematic diagram of the appearance of the magnesium-lithium alloy with a sealing layer on the surface obtained in step 4 of the embodiment of the present invention;

[0047] Figure 4 Schematic diagram of the appearance of the magnesium-lithium alloy with a primer layer on the surface obtained in step 5.1 of the embodiment of the present invention;

[0048] Figure 5 Schematic diagram of the appearance of the magnesium-lithium alloy with a topcoat layer obtained in step 5.2 of the embodiment of the present invention;

[0049] Figure 6It is a schematic diagram of the appearance of the magnesium-lithium alloy with a topcoat layer obtained in step 5.2 of the embodiment of the present invention after 10 wet heat tests. DETAILED DESCRIPTION

[0050] Embodiment 1

[0051] A surface modification method for a magnesium-lithium alloy comprises the following steps:

[0052] Step 1: Pre-treat the magnesium-lithium alloy body

[0053] like Figure 1 As shown, the magnesium-lithium alloy body is machined into a preset size, and then degreased, cleaned and dried in sequence; in this embodiment, the magnesium-lithium alloy body is machined with a groove;

[0054] Step 2: Prepare micro-arc oxidation electrolyte

[0055] Dissolve vanadate, fluoride and phosphate in deionized water to prepare a micro-arc oxidation electrolyte; wherein the mass fraction of vanadate is 8-10%, the mass fraction of fluoride is 8-10%, and the mass fraction of phosphate is 28-32%; in this embodiment, the vanadate is sodium vanadate with a mass fraction of 8%, the fluoride is sodium fluoride with a mass fraction of 8%, and the phosphate is sodium phosphate with a mass fraction of 30%;

[0056] Step 3: Micro-arc oxidation treatment

[0057] Step 3.1, using the magnesium-lithium alloy body pretreated in step 1 as an anode and an inert metal plate as a cathode, immersing the anode and the cathode in the micro-arc oxidation electrolyte obtained in step 2 to form an electrolytic cell; in this embodiment, the inert metal plate is a stainless steel plate;

[0058] Step 3.2: Use a single pulse power supply to energize the electrolytic cell formed in step 3.1, and control the current density to 1.5A / dm 2 , the frequency is 300 Hz, and the temperature of the micro-arc oxidation electrolyte is 20 ° C. The anode is subjected to micro-arc oxidation treatment for 10 minutes. Figure 2 As shown, a magnesium-lithium alloy with a micro-arc oxidation layer on the surface is obtained, the thickness of the micro-arc oxidation layer is 22 μm, and the micro-arc oxidation layer is a black continuous and uniform film layer with consistent glossiness;

[0059] Step 4: Sealing

[0060] Step 4.1, cleaning and drying the magnesium-lithium alloy after micro-arc oxidation treatment in step 3.2;

[0061] Step 4.2, pre-bake the magnesium-lithium alloy dried in step 4.1 for 15 minutes at a pre-bake temperature of 110°C, then spray the inner surface of the groove of the magnesium-lithium alloy with a silane sealing liquid, bake for 8 minutes at a baking temperature of 110°C, turn over, spray the unsprayed surface of the magnesium-lithium alloy with a silane sealing liquid, and cure it at a curing temperature of 170°C for 35 minutes, and finally cool it to room temperature. Figure 3 As shown, a magnesium-lithium alloy with a sealing layer on the surface is obtained, the sealing layer has a thickness of 2 μm, and the sealing layer is a continuous and uniform transparent layer with a small amount of gloss, and there is no sagging, no accumulation, and no debris on the surface;

[0062] Step 5: Spray treatment and wet heat test

[0063] Step 5.1, spray the magnesium-lithium alloy surface obtained in step 4.2 with a magnesium alloy special primer with a viscosity of 18s, then bake it at a temperature of 100°C for 1h, cool it to room temperature, and repeat the spraying and baking operations once, such as Figure 4 As shown, a magnesium-lithium alloy with a primer layer on the surface is obtained, the thickness of the primer layer is 35 μm, and the black micro-arc oxidation layer is completely covered;

[0064] Step 5.2: Spray the surface of the magnesium-lithium alloy obtained in step 5.1 with an acrylic polyurethane topcoat having a viscosity of 18s, and then bake at a temperature of 100°C for 1h. After cooling to room temperature, repeat the spraying and baking operations once. Figure 5 As shown, a magnesium-lithium alloy with a topcoat layer on the surface is obtained, and the total thickness of the topcoat layer and the primer layer is 100 μm;

[0065] Step 5.3: Perform a wet heat test on the magnesium-lithium alloy obtained in step 5.2. The specific steps are as follows:

[0066] Step A1, placing the magnesium-lithium alloy obtained in step 5.2 into a wet heat test chamber, and setting the initial temperature of the chamber to 30° C.;

[0067] Step A2: within 2 hours, the temperature in the box is raised from 30°C to 60±2°C, and the relative humidity is raised to 95%, and then maintained at 60±2°C and 95% for 6 hours;

[0068] Step A3, within 8 hours, the temperature in the box is cooled from 60±2°C to 30±2°C, and the relative humidity is maintained above 85% during the cooling period. When the temperature drops to 30±2°C, the relative humidity is controlled to 95%, and maintained at this temperature and relative humidity for 8 hours;

[0069] Step A4, repeat step A2 and step A3 until 10 cycles are completed, take out the magnesium-lithium alloy, observe the surface condition of the magnesium-lithium alloy after the wet heat test, and judge whether it is qualified. If not, the magnesium-lithium alloy is regarded as waste, and a magnesium-lithium alloy body is selected again, and return to step 1 until the current magnesium-lithium alloy passes the wet heat test; if so, the surface modification of the magnesium-lithium alloy is completed. Figure 6 As shown, after 10 wet heat tests, the surface of the modified magnesium-lithium alloy obtained in this embodiment is intact, without defects such as blistering, peeling, and falling off, indicating that it is qualified, has good protective performance, and has good wet heat resistance. Otherwise, it is unqualified, has poor protective performance, and has poor wet heat resistance.

[0070] Embodiment 2

[0071] The modification method of this embodiment is the same as that of the first embodiment, except that:

[0072] In step 2, potassium vanadate, potassium fluoride and potassium phosphate are dissolved in deionized water to prepare a micro-arc oxidation electrolyte; wherein the mass fraction of potassium vanadate is 9%, the mass fraction of potassium fluoride is 9%, and the mass fraction of potassium phosphate is 32%;

[0073] In step 3.2, the current density is 2.0A / dm 2 , the frequency is 350 Hz, the temperature of the micro-arc oxidation electrolyte is 25 ° C, the micro-arc oxidation treatment time is 9 min, the thickness of the micro-arc oxidation layer is 20 μm, and the schematic diagram of the magnesium-lithium alloy with a micro-arc oxidation layer is shown in FIG. Figure 2 ;

[0074] In step 4.2, the pre-baking temperature is 105°C, the pre-baking time is 20 minutes, the baking temperature is 105°C, the baking time is 10 minutes, the curing temperature is 175°C, the curing time is 30 minutes, the thickness of the sealing layer is 1 μm, and the schematic diagram of the magnesium-lithium alloy with a sealing layer on the surface is shown in FIG. Figure 3 ;

[0075] In step 5.1, the viscosity of the primer for magnesium alloy is 20s, the baking temperature is 105°C, the baking time is 50min, the thickness of the primer layer is 30μm, and the schematic diagram of the magnesium-lithium alloy with the primer layer on the surface is shown in FIG. Figure 4 ;

[0076] In step 5.2, the viscosity of the acrylic polyurethane topcoat is 21s, the baking temperature is 105°C, the baking time is 50min, the total thickness of the topcoat layer and the primer layer is 80μm, and the schematic diagram of the magnesium-lithium alloy with the topcoat layer is shown in FIG. Figure 5 .

[0077] Embodiment 3

[0078] The modification method of this embodiment is the same as that of the first embodiment, except that:

[0079] In step 2, magnesium vanadate, magnesium fluoride and magnesium phosphate are dissolved in deionized water to prepare a micro-arc oxidation electrolyte; wherein the mass fraction of magnesium vanadate is 10%, the mass fraction of magnesium fluoride is 10%, and the mass fraction of magnesium phosphate is 28%;

[0080] In step 3.2, the current density is 2.5A / dm 2 , the frequency is 400 Hz, the temperature of the micro-arc oxidation electrolyte is 23 ° C, the micro-arc oxidation treatment time is 8 min, the thickness of the micro-arc oxidation layer is 25 μm, and the schematic diagram of the magnesium-lithium alloy with a micro-arc oxidation layer on the surface is shown in FIG. Figure 2 ;

[0081] In step 4.2, the pre-baking temperature is 115°C, the pre-baking time is 10 min, the baking temperature is 115°C, the baking time is 5 min, the curing temperature is 165°C, the curing time is 40 min, the thickness of the sealing layer is 3 μm, and the schematic diagram of the magnesium-lithium alloy with a sealing layer on the surface is shown in FIG. Figure 3 ;

[0082] In step 5.1, the viscosity of the primer for magnesium alloy is 22s, the baking temperature is 95°C, the baking time is 70min, the thickness of the primer layer is 40μm, and the schematic diagram of the magnesium-lithium alloy with the primer layer on the surface is shown in FIG. Figure 4 ;

[0083] In step 5.2, the viscosity of the acrylic polyurethane topcoat is 24s, the baking temperature is 95°C, the baking time is 70min, the total thickness of the topcoat layer and the primer layer is 120μm, and the schematic diagram of the magnesium-lithium alloy with the topcoat layer obtained is shown in FIG. Figure 5 .

[0084] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A surface modification method for a magnesium-lithium alloy, characterized in that: The following steps are involved: Step 1, pretreating the magnesium-lithium alloy body; Step 2, dissolving vanadate, fluoride and phosphate in deionized water to prepare a micro-arc oxidation electrolyte; wherein the mass fraction of vanadate is 8-10%, the mass fraction of fluoride is 8-10%, and the mass fraction of phosphate is 28-32%; Step 3, using the magnesium-lithium alloy body pretreated in step 1 as an anode and the inert metal plate as a cathode, immersing the anode and the cathode in the micro-arc oxidation electrolyte to form an electrolytic cell; then energizing the electrolytic cell to perform micro-arc oxidation treatment to obtain a magnesium-lithium alloy with a micro-arc oxidation layer on the surface; Step 4: Sealing Step 4.1, cleaning and drying the magnesium-lithium alloy after micro-arc oxidation treatment in step 3; Step 4.2, pre-baking the magnesium-lithium alloy dried in step 4.1, then spraying the surface of the magnesium-lithium alloy with a silane sealing liquid, and baking it, turning it over, spraying the unsprayed surface of the magnesium-lithium alloy with a silane sealing liquid, and curing it, and finally cooling it to room temperature to obtain a magnesium-lithium alloy with a sealing layer on the surface; Step 5: Spray treatment and wet heat test Step 5.1, spraying the surface of the magnesium-lithium alloy obtained in step 4.2 with a special primer for magnesium alloy, and baking, after cooling to room temperature, repeating the spraying and baking operations once to obtain a magnesium-lithium alloy with a primer layer on the surface; Step 5.2, spraying the surface of the magnesium-lithium alloy obtained in step 5.1 with an acrylic polyurethane topcoat, baking, cooling to room temperature, repeating the spraying and baking operations once, and obtaining a magnesium-lithium alloy with a topcoat layer on the surface; Step 5.3, perform a wet heat test on the magnesium-lithium alloy obtained in step 5.2 to determine whether it is qualified. If not, the magnesium-lithium alloy is treated as waste, and a new magnesium-lithium alloy body is selected, and the process returns to step 1 until the current magnesium-lithium alloy passes the wet heat test; if so, the surface modification of the magnesium-lithium alloy is completed.

2. The surface modification method of magnesium-lithium alloy according to claim 1, characterized in that: Step 4.2 is as follows: Under the condition of pre-baking temperature of 105-115°C, the magnesium-lithium alloy dried in step 4.1 is pre-baked for 10-20 minutes, and then the surface of the magnesium-lithium alloy is sprayed with silane sealing liquid, and baked for 5-10 minutes under the condition of baking temperature of 105-115°C. After turning over, the unsprayed surface of the magnesium-lithium alloy is sprayed with silane sealing liquid again, and cured at a curing temperature of 165-175°C and a curing time of 30-40 minutes. Finally, it is cooled to room temperature to obtain a magnesium-lithium alloy with a sealing layer on the surface, and the thickness of the sealing layer is 1μm to 3μm.

3. The surface modification method of magnesium-lithium alloy according to claim 1 or 2, characterized in that: Step 3 specifically includes the following steps: Step 3.1, using the magnesium-lithium alloy body pretreated in step 1 as an anode and an inert metal plate as a cathode, immersing the anode and the cathode in the micro-arc oxidation electrolyte to form an electrolytic cell; Step 3.2: Use a single pulse power supply to energize the electrolytic cell and control the current density to be 1.5-2.5 A / dm 2 , the frequency is 300-400 Hz, and the temperature of the micro-arc oxidation electrolyte is 20-25° C. The anode is subjected to micro-arc oxidation treatment for 8-10 minutes to obtain a magnesium-lithium alloy with a micro-arc oxidation layer on the surface, and the thickness of the micro-arc oxidation layer is 20 μm-25 μm.

4. The surface modification method of magnesium-lithium alloy according to claim 3, characterized in that: Step 5.1 is specifically to spray the surface of the magnesium-lithium alloy obtained in step 4.2 with a special primer for magnesium alloy with a viscosity of 18 to 22s, and then bake it at a temperature of 95 to 105°C for 50 to 70 minutes. After cooling to room temperature, the spraying and baking operations are repeated once to obtain a magnesium-lithium alloy with a primer layer on the surface, and the thickness of the primer layer is 30 μm to 40 μm; Specifically, step 5.2 is to spray the surface of the magnesium-lithium alloy obtained in step 5.1 with an acrylic polyurethane topcoat with a viscosity of 18 to 24s, and then bake it at a temperature of 95 to 105°C for 50 to 70 minutes. After cooling to room temperature, the spraying and baking operations are repeated once to obtain a magnesium-lithium alloy with a topcoat layer on the surface. The total thickness of the topcoat layer and the primer layer is 80 μm to 120 μm.

5. The surface modification method of magnesium-lithium alloy according to claim 4, characterized in that: Step 5.3 specifically includes the following steps: Step A1, placing the magnesium-lithium alloy obtained in step 5.2 into a wet heat test chamber, and setting the initial temperature of the chamber to 30° C.; Step A2: within 2 hours, the temperature in the box is raised from 30°C to 60±2°C, and the relative humidity is raised to 95%, and then maintained at 60±2°C and 95% for 6 hours; Step A3, within 8 hours, the temperature in the box is cooled from 60±2°C to 30±2°C, and the relative humidity is maintained above 85% during the cooling period. When the temperature drops to 30±2°C, the relative humidity is controlled to 95%, and maintained at this temperature and relative humidity for 8 hours; Step A4, repeat step A2 and step A3 until at least 10 cycles are completed, take out the magnesium-lithium alloy, and determine whether it is qualified. If not, the magnesium-lithium alloy is treated as waste, and a magnesium-lithium alloy body is reselected, and return to step 1 until the current magnesium-lithium alloy passes the wet heat test; if so, the surface modification of the magnesium-lithium alloy is completed.

6. The surface modification method of magnesium-lithium alloy according to claim 1, characterized in that: Step 2 is as follows: Sodium vanadate, sodium fluoride and sodium phosphate are dissolved in deionized water to prepare a micro-arc oxidation electrolyte; wherein the mass fraction of sodium vanadate is 8%, the mass fraction of sodium fluoride is 8%, and the mass fraction of sodium phosphate is 30%.

7. The surface modification method of magnesium-lithium alloy according to claim 4, characterized in that: Step 4.2 is as follows: Under the condition of pre-baking temperature of 110°C, the magnesium-lithium alloy dried in step 4.1 is pre-baked for 15 minutes, and then the surface of the magnesium-lithium alloy is sprayed with silane sealing liquid. Under the condition of baking temperature of 110°C, it is baked for 8 minutes. After turning over, the unsprayed surface of the magnesium-lithium alloy is sprayed with silane sealing liquid again, and cured at a curing temperature of 170°C and a curing time of 35 minutes. Finally, it is cooled to room temperature to obtain a magnesium-lithium alloy with a sealing layer on the surface, and the thickness of the sealing layer is 1μm to 3μm.

8. The surface modification method of magnesium-lithium alloy according to claim 7, characterized in that: Step 3.2 is as follows: The electrolytic cell was energized by a single pulse power supply, and the current density was controlled to be 1.5A / dm 2 , the frequency is 300 Hz, and the temperature of the micro-arc oxidation electrolyte is 20° C. The anode is subjected to micro-arc oxidation treatment for 10 minutes to obtain a magnesium-lithium alloy with a micro-arc oxidation layer on the surface, and the thickness of the micro-arc oxidation layer is 20 μm to 25 μm.

9. The surface modification method of magnesium-lithium alloy according to claim 8, characterized in that: In step 5.1, the viscosity of the magnesium alloy special primer is 18s, the baking temperature is 100°C, and the baking time is 1h; In step 5.2, the viscosity of the acrylic polyurethane topcoat is 18s, the baking temperature is 100°C, and the baking time is 1h.

10. The surface modification method of magnesium-lithium alloy according to claim 9, characterized in that: Step 1 is as follows: The magnesium-lithium alloy body is machined into a preset size and then degreased, cleaned and dried in sequence.

Citation Information

Patent Citations

  • Surface treatment method for magnesium-lithium-based alloy dark green protective coating

    CN109440165A

  • Composition for forming magnesium-lithium alloy surface anticorrosive coating system and preparation method of anticorrosive coating system

    CN112029394A

  • Magnesium alloy surface composite coating and preparation method thereof

    CN113897655A

  • Preparation method of MAO film on surface of magnesium alloy

    CN118563385A